HUBUNGAN ANTARA EFIKASI DIRI UNTUK BERARGUMENTASI DENGAN KEMAMPUAN BERPIKIR KRITIS CALON GURU AKUNTANSI - Fahrizka Danindra; Nurhasan Hamidi (STKIP Subang, 2026)
This study aims to determine the relationship between self-efficacy for argumentation and critical thinking skills in Accounting Education students at Sebelas Maret University. This study uses a quantitative correlational approach with a survey method. The study population was 250 active Accounting Education students at Sebelas Maret University in the 2022, 2023, and 2024 classes. The study sample was 154 respondents determined using the proportionate stratified random sampling technique with the Slovin formula. Data collection techniques used tests and questionnaires. The critical thinking skills instrument used the CTSS (Critical Thinking Standards Scale) developed by Aybek et al. (2015), while the self-efficacy for argumentation instrument used the SEAS (Self-Efficacy for Argumentation Scale) developed by Kiran (2019). Data analysis techniques used descriptive analysis, normality tests, linearity tests, simple correlation tests, partial statistical tests (t), and coefficients of determination. The results of the study indicate a positive and significant relationship between self-efficacy for argumentation and critical thinking skills of Accounting Education students at Sebelas Maret University. The results of the partial statistical test (t) showed a significance value of 0.002, thus the research hypothesis was accepted. The coefficient of determination value of 0.059 indicates that self-efficacy for argumentation contributes 5.9% to critical thinking skills, while the remainder is influenced by other factors outside the study. Students with high self-efficacy in argumentation tend to be more confident in presenting and defending arguments, thus demonstrating better critical thinking skills